Troubled road to the first spectrum auction in Poland - Jerzy Kubasik (International Telecommunications Society (ITS), 2014)
So far no general exclusive frequency licenses have been granted in Poland through an auction. In the Regulatory Strategy until 2015, the President of the Office of Electronic Communications pointed to auction as a method of choosing companies which will be granted frequency licenses from 800 MHz band (so called digital dividend). Initially, the auction has been scheduled to take place at the turn of 2013 and 2014, and was considered the biggest event of 2014 on the Polish telecommunications market. The article presents the main as-sumptions of the first ever spectrum auction in Poland on the basis of materials for auction assumptions' consultations, auction documentation, opinions of entities involved that have been submitted during consultations as well as the position of the President of UKE. The au-thor focuses on threats to execution of the auction itself as well as implementation of its re-sults. The text is preceded by a short description of the Polish telecommunications market, especially in terms frequencies owned by the main players on this market, including their joint ventures and capital connections.
Keywords: 330; regulation; spectrum auction; mobile services; LTE